WHATSAPP TO TEACH ENGLISH REMOTELY IN A LOW-TECH CLASS: TEACHER’S PERSPECTIVE - Fitriani Fitriani (Journal of English Education and Linguistics, 2020)
This study aims at addressing English teacher’s perspective about integrating WhatsApp (WA) into a university-level English class in STAIN Mandailing Natal. The data includes interviews with the teacher and observation on class postings in WA group and student-teacher timeline for four meetings. The data were analyzed qualitatively, and interpretively, resulting in three emerging themes about the WA to teach English remotely in low-tech classroom: the implementation of WA for online teaching, managing online learning activities in WA group and teacher’s constrains in applying WA in teaching online. The result of analysis indicates that WA is considered effective to teach English remotely in a limited internet connection classroom. With some adjustments to the instructional design, teaching and learning process could run well. However, due to the lack of students-teacher direct interaction, virtual class could not go as engaging as face-to-face learning in the classroom.